Blind signature scheme based on trusted platform computation module - Wen-ting HUANG; Ling-ling TONG; Yong-jian WANG (Tongxin xuebao)
For the key leak problem in identity-based blind signature, a blind signature scheme based on the trusted plat-form control module (TPCM) was presented. The message which will be signed is unknown to the signer, and the infor-mation of the signature cannot be tracked. In the blind signature scheme, the secret share distribution center and the TPCM cooperate to generate the user's signature key, and the user's private key is not alone to be produced. So it solves the key escrow problem, and can also be effective to prevent disclosure of the user's key and protect the user's anonymity and the no track of the signature. Finally random oracle was used to prove the security of the scheme. Compared with the traditional scheme, the proposed scheme has better computational efficiency.